Supporting English-speaking Children and Families in the Gaspé and Magdalen Islands 2017-2020 - Community Health and Social Services Network (CHSSN); Council for Anglophone Magdalen Islanders (CAMI); Vision Gaspé-Percé Now; Committee for Anglophone Social Action (CASA) (2017)
The official language minority community of this region has the poorest socioeconomic status in Canada when aspects such as low education levels, unemployment and low income tendencies are analyzed. Children are particularly affected by this status. Children ages 0 to 5 make up 6.6% of the total English-speaking population.
Keywords: Official Language Minority Community (OLMC)

Supporting English-speaking Children and Families in the Gaspé and Magdalen Islands - Community Health and Social Services Network (CHSSN) (2019)
Bright Beginnings is an adapted approach to supporting English-speaking children and families in the Gaspé and Magdalen Islands. It originated through a collaboration between CASA, CAMI and VGPN who began to work with regional and local partners to better adapt programs and services to support English- speaking children 0 to 5 years old and their families. This approach has been adopted by the CHSSN as a provincial framework for English- speaking communities.

Soutenir les enfants et les familles anglophones en Gaspésie et aux Îles-de-la-Madeleine - Community Health and Social Services Network (CHSSN) (2019)
Bright Beginnings est une approche adaptée pour aider les enfants et les familles d’expression anglaise de la Gaspésie et des Îles-de-la-Madeleine. L’initiative est née d’une collaboration entre CASA, CAMI et VGPN, qui ont commencé à travailler avec des partenaires régionaux et locaux pour mieux adapter les programmes et les services afin de soutenir les enfants d’expression anglaise de 0 à 5 ans et leurs familles. Le Réseau communautaire de santé et de services sociaux (RCSSS) a adopté cette approche comme cadre de référence provinciale pour les communautés d’expression anglaise.

Report on the Health and Social Services Priorities of English-speaking Communities in Quebec - Carter, James; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
In July 2017, the CHSSN submitted the present report to the Quebec Ministry of Health and Social Services inviting it to undertake consultations with key public institutions and community representatives with respect to the recommendations. The objective was to ensure that a proposal to Health Canada reflected the shared commitment of Quebec and its English-speaking communities to work in partnership to improve access to health and social services in English. In its reply to the CHSSN in October 2017 (Appendix), the Ministry supported the recommendations in accordance with comments reflecting the results of its consultations with the public institutions. To support Health Canada in its mandate to prepare a new Contribution Program, the sponsoring organizations of the twenty recognized community health and social services networks along with the CHSSN are submitting the present report and recommendations reflecting the continuity of results of the last federal contribution and emergence of new priorities for the period ahead.
Keywords: Official Language Minority Community (OLMC)

Profile of English-speaking Youth : Gaspésie-Îles-de-la-Madeleine - Richardson, Mary; Zettl, Mary; Harrison, Kim (Community Health and Social Services Network (CHSSN), 2020)
Three community organizations commissioned this profile of the situation of young people in the Gaspésie-Îles-de-la-Madeleine region: the Committee for Anglophone Social Action (CASA), the Council for Anglophone Magdalen Islanders (CAMI) and Vision Gaspé-Percé Now. A study grounded in community-based participatory action research was developed, with the goal of hearing directly from young people about their realities in order to take action on issues affecting them in the region’s communities. A mixed methods approach combined an on-line survey with focus group discussions exploring questions related to out-migration, education, employment, social life, services and more. A total of 438 young people filled out the survey and nine FGD were held in a total of six communities (with a total of 82 youth).

Les communautés anglophones de la Gaspésie-Îles-de-la-Madeleine : Un profil régional - Committee for Anglophone Social Action (CASA) (2018)

Inter-Regional Access to Specialized Health and Social Services for English-speakers from Eastern Quebec - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This project was developed to better understand the experience and needs of English speakers from the eastern regions of Quebec (Gaspésie - Îles-de-la-Madeleine, the North Shore, including the Lower North Shore, and the Lower Saint-Lawrence) as concerns extra-regional health and social services. The specific challenges facing this official language minority community were known only anecdotally, but needed to be better understood before effective action could be taken to address the needs of this population.
Keywords: Official Language Minority Community (OLMC)

Evaluation Report - Holley, Paul (Youth for Youth Québec (Y4Y Québec), 2020)
The following evaluation report fulfills a key deliverable of a broader project funded by Canadian Heritage and titled Best Practices in Community Engagement for the English Speaking Youth Population in Quebec, which was implemented by Youth 4 Youth (Y4Y) Quebec from April 1, 2019 to March 31, 2020. The key objective of this project was to boost youth engagement and participation in political and community life in Quebec. Y4Y successfully accomplished this objective by engaging over 1,000 youth through a series of 30 community consultations, 12 focus groups, and a youth survey delivered on-line and in-person with 520 respondents. The focus of this report is on the key findings from the survey, which targeted Englishspeaking youth ages 16 to 30 from across the province and collected quantitative and qualitative information on youth media consumption and community engagement activities. A gender-based analysis of key survey findings was also conducted and is presented in this report along with a set of recommendations for community organizations serving Quebec’s English-speaking youth population.

Evaluation of Community Services for English-speaking Seniors in Gaspé-Magdalen Islands - Richardson, Mary; Brown, Cathy; Burke, Helena; Synnott, Jessica (Community Health and Social Services Network (CHSSN), 2019)
This evaluation was undertaken by request of all three organizations. It follows an earlier evaluation completed in 2013 covering a smaller number of activities, by the same author. The evaluation was designed to take into account a) information on the wellness sessions (content, attendance, frequency, etc.); b) the perspectives of seniors; and c) the perspectives of the facilitators (workers). The following sources of information were used: a) attendance records; b) an online survey filled out in January-March 2019 by 141 seniors; and c) interviews conducted by the author, virtually, in February 2019 with seven facilitators and outreach workers.
Keywords: Official Language Minority Community (OLMC)

Évaluation des services communautaires pour les ainées et aînés d'expression anglaise de Gaspésie-Îles-de-la-Madeleine - Richardson, Mary; Brown, Cathy; Burke, Helena; Synnott, Jessica (Community Health and Social Services Network (CHSSN), 2019)
La présente évaluation a été entreprise à la demande des trois organismes. Elle fait suite à une évaluation antérieure réalisée en 2013 par la même auteure et couvrant un nombre moins élevé d’activités. L’évaluation a été conçue pour prendre en compte : a) l’information sur les séances de bien-être (contenu, assiduité, fréquence, etc.); b) le point de vue des personnes âgées; et c) le point de vue des animatrices (travailleuses). Les sources d’information suivantes ont été utilisées : a) relevés de présence; b) un sondage en ligne rempli en janviermars 2019 par 141 aînés; et c) des entrevues menées virtuellement par l’auteure en février 2019 avec sept animatrices et travailleuses de proximité.
Keywords: Official Language Minority Community (OLMC)

English-speaking Communities of the Gaspésie – Îles-de-la-Madeleine: A Regional Profile - Richardson, Mary; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)

Community Mobilization Model for Improving the Health and Vitality of English-Speaking Communities in Quebec - Kueber, Russell (Community Health and Social Services Network (CHSSN), 2019)
This brief description of a "Community Mobilization Model for Improving the Health and Vitality of English-speaking Communities in Quebec" includes a condensed background of English-speaking communities. It also includes a short description of some key concepts used in the model. The model is designed to communicate the approach taken by community helath and social services networks, which positions them as drivers of change in mobilizing English-speaking communities.

CHSSN Community Radio Project 2007-2008 - Community Health and Social Services Network (CHSSN) (Community Health and Social Services Network (CHSSN), 2008)
In winter 2007, the CHSSN carried out a pilot project in conjunction with Townshippers’ Association to disseminate community health information via community radio to test the efficacy of using this medium to extend the outreach of the Network Partnership Initiative (NPI). Two call-in shows – Dependencies and Mental Health – were broadcast by CJMQ-FM in Lennoxville, and an edited recording of the show on Dependencies was re-broadcast on CJAS in St-Augustin. Based on the success of the 2007 pilot, for winter 2008 the community radio project was expanded to include more regions, a wider range of informational programming and Internet dissemination.
Keywords: Official Language Minority Community (OLMC)

Bright Beginnings Project Descriptions - Community Health and Social Services Network (CHSSN) (2019)